THE ECONOMIC GROWTH EFFECTS OF WAR AND CIVIL WAR IN IRAQ - Rudolph, Stephan (Journal of European Economy, 2017)
The purpose of this paper is to study the effects of war and civil war in Iraq on the country’s economic growth in a theoretical way. A simplified form of the neo-classical growth model by Solow (1956) is used and the channels are worked out, through which war and civil war could affect the single parameters of the applied growth model. It appears that, from a theoretical point of view, the destruction of the capital stock by bombings is likely to gain higher growth rates by enfolding the economy’s forces of recovery. But it also appears that these forces are reduced by disruption, diversion, dissaving and portfolio substitution effects and lower Iraq’s opportunities for a full recovery.